Impact of climate and management variables on stone pine (Pinus pinea L.) growing in Chile - Muñoz, Verónica Loewe (2015)
Pinus pinea is an interesting species especially for its fruit production, which depends upon vegetative growth. Growth of this species was analyzed along a climatic gradient in Chile, in all sites where it was planted in the last century. Three macrozones (MZs) located in the north, south and coastal range were identified according to height and DBH growth rates. We also examined growth in relation to several climatic variables (annual and seasonal temperatures, thermal oscillation, rainfall and a hydric index measuring water stress) and two cultural practices (irrigation and pruning). The relative contribution of each variable on growth measurements was assessed through regression trees and linear models. Growth of stone pine showed marked differences among the three MZs. In the South MZ, growth rate was the highest for height (0.35myear-1) and DBH (1.50cmyear-1), whereas in the Dry Coast MZ, the species showed the lowest growth rate in height (0.23myear-1) and DBH (0.87cmyear-1). Temperature and rainfall had a high significant impact on height growth, which was favored by an annual average temperature below 14°C, with high winter thermal oscillation (>14°C), spring water deficit lower than 400mm and annual rainfall over 1400mmyear-1. DBH growth was also favored by an average annual temperature below 14°C. Significant effects of pruning and irrigation were found. Stone pine growth throughout Chile was high compared to growth rates reported for other countries. However, in light of climate change, we should expect a reduction in growth rates especially in the North and Dry Coast MZs. Heat tolerance is proposed as a key breeding trait for increasing potential growth of stone pine.